Silicon Sensors and Actuators The Feynman Roadmap - Vigna, Benedetto; Ferrari, Paolo; Villa, Flavio Francesco; Lasalandra, Ernesto; Zerbini, Sarah; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book thoroughly reviews the present knowledge on silicon micromechanical transducers and addresses emerging and future technology challenges. Readers will acquire a solid theoretical and practical background that will allow them to analyze the key performance aspects of devices, critically judge a fabrication process, and then conceive and design new ones for future applications. Envisioning a future complex versatile microsystem, the authors take inspiration from Richard Feynman$1 (Bs visionary talk (3z(BThere is Plenty of Room at the Bottom(3y (Bto propose that the time has come to see silicon sensors as part of a (3z(BFeynman Roadmap(3y (Binstead of the (3z(BMore-than-Moore(3y (Btechnology roadmap. The sharing of the author$1 (Bs industrially proven track record of development, design, and manufacturing, along with their visionary approach to the technology, will allow readers to jump ahead in their understanding of the core of the topic in a very effective way. Students, researchers, engineers, and technologists involved in silicon-based sensor and actuator research and development will find a wealth of useful and groundbreaking information in this book.s
1. Silicon as Sensor Material -- 2. Epitaxial Growth -- 3. Thin Film Deposition -- 4. Thin Films Characterization & Metrology -- 5. Dry silicon etch -- 6. Lithography -- 7. HF Release -- 8. Galvanic growth -- 9. Wet Etch and Cleaning -- 10. Piezoelectric materials -- 11. Wafer to wafer Bonding.-12. Linear and non linear mechanichs in MEMS -- 13. Inertial sensors -- 14. Magnetometer -- 15. MEMS microphones -- 16. Pressure Sensors -- 17. Enviromental Sensors -- 18. Mirror -- 19. Piezo ink jet printers -- 20. Speakers -- 21. Autofocus -- 22. Electronic sensors front-end -- 23. Electronic Interfaces for actuators -- 24. Package -- 25. Testing -- 26. Reliability -- 27. The future of sensor and actuators.
Keywords: Electronics; Microtechnology; Microelectromechanical systems; Electronic circuits; Materials; Electronics and Microelectronics, Instrumentation; Microsystems and MEMS; Electronic Circuits and Systems; Materials Engineering; Electronic Circuits and Systems; Silicon diodes; Actuators